2016
DOI: 10.18632/oncotarget.12067
|View full text |Cite
|
Sign up to set email alerts
|

Binding of human recombinant mutant soluble ectodomain of FGFR2IIIc to c subtype of FGFRs: implications for anticancer activity

Abstract: FGFRs are considered essential targets for cancer therapy. We previously reported that msFGFR2c, a Ser252Trp mutant soluble ectodomain of FGFR2IIIc, inhibited tumor growth by blocking FGF signaling pathway. However, the underlying molecular mechanism is still obscure. In this study, we reported that msFGFR2c but not wild-type soluble ectodomain of FGFR2IIIc (wsFGFR2c) could selectively bind to c subtype of FGFRs in the presence of FGF-2. Thermodynamic analysis demonstrated that msFGFR2c bound to wsFGFR2c in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Owing to their crucial role in pulmonary fibrosis (Corti et al 1996;Ehrhardt et al 2005;Fujino et al 2011;Liu et al 2016), mouse primary AE2 cells were examined in this study. Here, we found that the addition of fibroblast medium of MRC-5 cells increased N-cadherin and a-SMA levels and decreased E-cadherin levels in AE2 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their crucial role in pulmonary fibrosis (Corti et al 1996;Ehrhardt et al 2005;Fujino et al 2011;Liu et al 2016), mouse primary AE2 cells were examined in this study. Here, we found that the addition of fibroblast medium of MRC-5 cells increased N-cadherin and a-SMA levels and decreased E-cadherin levels in AE2 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies targeting FGFs and FGFRs, ligand traps (soluble FGFR ligand binding domains), small‐molecule FGFR inhibitors, and aptamers are being developed for the treatment of a variety of genetic, metabolic, and oncologic human diseases (Table 2) (Chioni & Grose, 2021; Grabner et al, 2015; Herbert et al, 2014; Ho et al, 2009; Liu et al, 2016; Ornitz & Itoh, 2015; Ornitz & Legeai‐Mallet, 2017; Presta et al, 2017; Szymczyk et al, 2021; Weaver & Bossaer, 2021). Among them, some medications including Burosumab, Erdafitnib, and Pemigatinib have been approved for therapeutic use by the US Food and Drug Administration (FDA).…”
Section: Development Of Fgf Pathway Inhibitors As Pharmaceuticalsmentioning
confidence: 99%
“…Soluble extracellular domains of FGFR1c, FGFR2b, FGFR2c, and FGFR3c have been developed as ligand trap inhibitors and have been evaluated in vivo (Blackwell et al, 2016; Garcia et al, 2013; Goncalves et al, 2020; Liu et al, 2016; Saint‐Laurent et al, 2018; Tolcher et al, 2016). As an example, mesothelioma and other lung cancers express high levels of FGF2 and FGFR1 (Marek et al, 2014; Wynes et al, 2014).…”
Section: Development Of Fgf Pathway Inhibitors As Pharmaceuticalsmentioning
confidence: 99%
“…A complete understanding of the role of FGFR signalling in breast cancer biology and of how FGFR signalling architecture adapts during breast cancer progression [250] or treatment with canonical strategies will then pave the way for discovering or improving novel strategies to benefit breast cancer patients. For instance, the use either of certain FGFs as therapeutics or of more specific ligand-trap molecules and isoform-specific FGFR inhibitors still needs further optimization [2,133,[251][252][253][254].…”
Section: What Is Missing From a Signalling Perspective?mentioning
confidence: 99%